Introductory Address on the Occasion of the Statistical and Social Inquiry Society of Ireland’s 175th Anniversary - Higgins, Michael D. (Statistical and Social Inquiry Society of Ireland, 2022)
Introductory Address on the Occasion of the Statistical and Social Inquiry Society of Ireland’s 175th Anniversary
read before the Society, 21st October 2021
Keywords: 314.15